Shyness, hormones, and quality of life among adults with schizophrenia. (4th May 2019) - Khalesi, Zahra; Jetha, Michelle K.; Poole, Kristie L.; Goldberg, Joel O.; Van Lieshout, Ryan J.; Schmidt, Louis A.
Abstract: Objective: Although individual differences in personality are known to influence quality of life in individuals with schizophrenia, relatively few studies have attempted to identify putative links underlying this relation. Methods: Here, we examined associations among temperamental shyness, hormones (ie baseline salivary cortisol and testosterone), and quality of life (QoL) measured in 42 stable outpatient adults with schizophrenia. Results: We found that baseline cortisol, but not testosterone, moderated the relation between shyness and QoL ( ß  = 1.09, p  = 0.004). Among individuals with relatively low baseline cortisol, higher shyness was associated with lower Intrapsychic Foundations QoL. Individuals with relatively higher baseline cortisol reported similar QoL scores irrespective of level of shyness. Conclusion: These preliminary results suggest that relatively lower baseline cortisol may be helpful to understanding the relation between temperament and Intrapsychic Foundations QoL in schizophrenia. The present findings are consistent with previous studies implicating relatively lower baseline cortisol levels in nonclinical samples of people who are shy and the negative downstream effects resulting from HPA axis dysregulation, and extends these prior findings to people with schizophrenia who are also shy.